Search for light scalar top-quark pair production in final states with two leptons with the ATLAS detector in √ s =7 TeV proton–proton collisions - Anduaga, Xabier Sebastián (2012)
A search is presented for the pair production of light scalar top quarks in √ s = 7 TeV proton–proton collisions recorded with the ATLAS detector at the Large Hadron Collider. This analysis uses the full data sample collected during 2011 running that corresponds to a total integrated luminosity of 4.7 fb−1. Light scalar top quarks are searched for in events with two opposite-sign leptons (e, μ), large missing transverse momentum and at least one jet in the final state. No excess over Standard Model expectations is found, and the results are interpreted under the assumption that the light scalar top decays to a b-quark in addition to an on-shell chargino whose decay occurs through a virtual W boson. If the chargino mass is 106 GeV, light scalar top-quark masses up to 130 GeV are excluded for neutralino masses below 70 GeV.